The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.5603/cj.a2016.0018
|View full text |Cite
|
Sign up to set email alerts
|

Time course of vascular response after an a priori strategy of bare metal stent implantation post-dilated with a paclitaxel-coated balloon: Implementation of a three-dimensional analysis algorithm with optical coherence tomography

Abstract: Background: An a priori combined therapy of a bare metal stent post-dilated with a paclitaxel--coated balloon (PCB) was investigated with optical coherence tomography (OCT) at p = 0.001; uncovered struts: 14.5 ± 14.8% vs. 2.0 ± 5.3%, p = 0.001 (Cardiol J 2016; 23, 3: 296-306)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…This could also explain the similar outcomes observed in our patients with or without dissection. A similar study on the time course of vascular response after implantation of bare‐metal stents after DCB dilation showed transient, severe, incomplete strut apposition after the procedure . A meta‐analysis comparing the outcomes of bare‐metal stent implantation after DCB with DES treatment also suggested that bail‐out stenting may be a predictor of poor late lumen loss and MACE .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This could also explain the similar outcomes observed in our patients with or without dissection. A similar study on the time course of vascular response after implantation of bare‐metal stents after DCB dilation showed transient, severe, incomplete strut apposition after the procedure . A meta‐analysis comparing the outcomes of bare‐metal stent implantation after DCB with DES treatment also suggested that bail‐out stenting may be a predictor of poor late lumen loss and MACE .…”
Section: Discussionmentioning
confidence: 82%
“…12 Briefly, the RESTORE SVD China study was a prospective, randomized, open-label, multicenter trial in which 230 eligible patients with visually-estimated reference vessel diameter (RVD) ≥2. 25 and ≤2.75 mm were randomized to undergo PCI with RESTORE DCB (Cardionovum, Bonn, Germany) or RESO-LUTE Integrity DES (Medtronic, Minneapolis, Minnesota) implantation in a 1:1 ratio stratified by diabetes and the number of lesions treated.…”
Section: Methodsmentioning
confidence: 99%
“…The OCTOPUS trial, which used optical coherence tomography, reported that DCB + BMS was associated with more pronounced neointimal proliferation than DES. [23,34] The IVUS study used intravascular ultrasound also showed more pronounced neointimal hyperplasia in the DCB + BMS group, leading to more revascularization than that in the DES group. [35] The reason for this finding is not yet satisfactorily explained.…”
Section: Discussionmentioning
confidence: 99%
“…However, properties of DCB´s should not be understood as “class effects” [28]. Current evidence for vessel wall expansion is the strongest for paclitaxel and is histologically proven as media wall thinning and cell necrosis in addition to inhibition of smooth muscle cells [18, 2931]. Out of the available paclitaxel-coated balloons, the Sequent Please™ DCB used in this study has been best investigated.…”
Section: Discussionmentioning
confidence: 99%
“…OCT images were acquired with an automated pullback of 20 mm/s (St. Jude Medical Ilumien™), analyzed offline and blinded to the coronary angiogram. A computational algorithm was applied for dissection and plaque analysis as described before: Plaque morphology was assessed according to the international consensus [17, 18]. Plaques and dissections were manually traced in each cross section, and according volumes were computed through the integral of cross-sectional measurements.…”
Section: Methodsmentioning
confidence: 99%